Analysis of brain functional response to cutaneous prickling stimulation by single fiber. Issue 4 (6th January 2021) - Wang, Qicai; Tao, Yuan; Sun, Tao; Sun, Fengxin; Jiang, Zhaohui; Jia, Zhao; Ding, Zuowei; Sun, Jie
Abstract: Background: It is now well understood that, as an uncomfortable sensation evoked by special fabric, prickle derives from the mechanical stimulation of protruding hairiness from fabric surface against the human skin, in which some nociceptors are easy to be triggered by stiff fiber ends. However, up to now, the neural mechanism of the brain for perceiving fabric‐evoked prickle is still unclear. Materials and Methods: In this work, A type of single‐fiber stimulus made from nylon filament was used to repetitively prick the skin of volar forearm at a specific frequency, and the technology of functional magnetic resonance imaging (fMRI) was adopted to detect the brain response synchronously. Results: The results show that repetitive prickling stimulation from the single fiber applied to the volar forearm aroused distributed activation in several brain regions, such as primary somatosensory cortex, secondary somatosensory cortex, motor cortex, bilateral occipital lobe, insular cortex, and ipsilateral limbic lobe. Although the brain activation distribution is similar to pain, the single fiber–evoked prickle sensation possesses unique activation characteristics in several brain regions. Conclusion: It is suggested that the sensation evoked by cutaneous prickling stimulation from single fiber belongs to a kind of multidimensional experience involving somatosensory, motor, emotional, cognitive, etc Our study constitutes an important step toward identifying the brain mechanism of fabric‐evoked prickle.